2013
DOI: 10.1111/cen.12249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lifestyle modification on serum chemerin concentration and its association with insulin sensitivity in overweight and obese adults with type 2 diabetes

Abstract: A 12-week intensive lifestyle intervention significantly decreased serum chemerin level compared to usual care. Decrease in serum chemerin level was associated with improved insulin sensitivity, and this may be involved in the beneficial effects of lifestyle intervention in overweight and obese type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 35 publications
(77 reference statements)
7
48
5
Order By: Relevance
“…The levels of chemerin, an adipokine identified fairly recently, were correlated with body mass index (BMI) and components of the metabolic syndrome in normal and overweight subjects [5,[7][8][9][10][11][12][13][14][15][16][17][18][19]. It has also been shown that the levels of chemerin in patients with metabolic syndrome are significantly correlated with BG, high density lipoprotein-cholesterol (HDL-C), CHOL, TG, CRP, fasting insulin and the homeostatic model assessment (HOMA) index [18,[20][21][22], whereas a negative correlation exists with the glomerular filtration rate (GFR) [23]. Studies also indicate that serum chemerin levels are significantly elevated in patients on chronic hemodialysis and are correlated with renal function [7].…”
Section: Discussionmentioning
confidence: 97%
“…The levels of chemerin, an adipokine identified fairly recently, were correlated with body mass index (BMI) and components of the metabolic syndrome in normal and overweight subjects [5,[7][8][9][10][11][12][13][14][15][16][17][18][19]. It has also been shown that the levels of chemerin in patients with metabolic syndrome are significantly correlated with BG, high density lipoprotein-cholesterol (HDL-C), CHOL, TG, CRP, fasting insulin and the homeostatic model assessment (HOMA) index [18,[20][21][22], whereas a negative correlation exists with the glomerular filtration rate (GFR) [23]. Studies also indicate that serum chemerin levels are significantly elevated in patients on chronic hemodialysis and are correlated with renal function [7].…”
Section: Discussionmentioning
confidence: 97%
“…A lifestyle modification of T2DM patients, through practice of regular physical exercise, even in a moderate rate, and healthy diet habits should be encouraged. Indeed, according to Kim et al, 15 12 weeks of intensive lifestyle modification, which included supervised exercise sessions, significantly decreased serum chemerin level, which was associated with an improvement in insulin sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…In overweight and obese type 2 diabetes patients chemerin levels are positively correlated with HOMA-IR and fasting insulin and negatively with insulin sensitivity index (ISI). Changes in the chemerin concentration during 12 weeks intensive lifestyle modification are independently and negatively correlated with changes in ISI and positively with changes in fasting plasma glucose and total cholesterol [37]. Weight-loss is mostly found to reduce chemerin and to improve insulin sensitivity [38].…”
Section: Serum Chemerin and Metabolic Syndromementioning
confidence: 99%